Uniqueness of approximate solutions to the Gelfand Levitan equation - A. Kincanon, Eric (International Journal of Applied Mathematical Research, 2020)
This brief paper considers a potential issue of using iterative solutions for the Gelfand-Levitan equation. Iterative solutions require approx-imation methods and this could lead to a loss of uniqueness of solutions. The calculations in this paper demonstrate that this is not the case and that uniqueness is preserved.Â Â